dampak Dampak negatif konsumsi pewarna makanan sintetis berlebihan terhadap kesehatan manusia - Aini, Roihana Qurotul (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the long-term impact of consuming synthetic dyes, specifically tartrazine and Rhodamin-B, on human health, particularly regarding snack foods widely consumed by children. The research employed a literature review and field survey approach to identify synthetic dye content in various popular snack products on the market. Findings indicate that continuous consumption of tartrazine and Rhodamin-B can lead to numerous health issues, including organ dysfunction, behavioral and digestive disorders, and hormonal imbalances. Analysis results show that many packaged foods contain synthetic dyes, with tartrazine and Rhodamin-B being the two most frequently used. The study also highlights the importance of stricter regulations and health education to raise public awareness and reduce the consumption of foods with harmful synthetic dyes.